1999
DOI: 10.1007/bf03012949
|View full text |Cite
|
Sign up to set email alerts
|

Prilocaine induces apoptosis in osteoblastic cells

Abstract: Purpose: To determine whether prilocaine, a local anesthetic, induces apoptosis in osteoblastic cells. Methods: After reaching subconfluence, human osteoblastic Saos-2 and HG63 cells and mouse osteoblastic MC3T3-E I cells were exposed for 48 hr to varying concentrations of prilocaine up to I 0 mM and the cytotoxicity of the cells was analyzed by phase-contrast microscopy and WST-I assay. Saos-2 cells treated for 48 hr with 5 mM prilocaine were stained with Hoechst 33342 and nuclear fragmentation was examined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
0
16
0
4
Order By: Relevance
“…However, bupivacaine was shown to have a more potent cytotoxic effect than ropivacaine on the same cell types [6]. Other local anesthetics appear to have similar effects on various cell types [9][10][11][12][13][14]. Prilocaine was found to induce apoptosis in mouse and human osteoblastic cells [11] and lidocaine was shown to inhibit the proliferation of normal human fibroblasts, endothelial cells and keratinocytes [12], while enhancing bleomycin A 2 cytotoxicity and DNA strand breakage in murine leukemia cells and human head and neck carcinoma cells [13] and imparing corneal wound healing [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, bupivacaine was shown to have a more potent cytotoxic effect than ropivacaine on the same cell types [6]. Other local anesthetics appear to have similar effects on various cell types [9][10][11][12][13][14]. Prilocaine was found to induce apoptosis in mouse and human osteoblastic cells [11] and lidocaine was shown to inhibit the proliferation of normal human fibroblasts, endothelial cells and keratinocytes [12], while enhancing bleomycin A 2 cytotoxicity and DNA strand breakage in murine leukemia cells and human head and neck carcinoma cells [13] and imparing corneal wound healing [14].…”
Section: Discussionmentioning
confidence: 99%
“…Other local anesthetics appear to have similar effects on various cell types [9][10][11][12][13][14]. Prilocaine was found to induce apoptosis in mouse and human osteoblastic cells [11] and lidocaine was shown to inhibit the proliferation of normal human fibroblasts, endothelial cells and keratinocytes [12], while enhancing bleomycin A 2 cytotoxicity and DNA strand breakage in murine leukemia cells and human head and neck carcinoma cells [13] and imparing corneal wound healing [14]. Dibucaine was shown to induce apoptosis in a neuroblastoma cell line [9] and in HL-60 [10] cells through activation of various caspases in conjunction with the release of cytochrome c from mitochondria induced by a processed product of Bid and depolarization of the mitochondrial membrane potential [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also known that they have other beneficial or adverse effects on a variety of cellular activities such as wound-healing, thrombosis, inflammatory responses, and cellular toxicity (4,5,16). One of the cellular toxicities of local anesthetics, an adverse effect, is an induction of necrosis or apoptosis in non-neuronal as well as neuronal cells in vivo and in vitro (4,10,12,22,27). It has been reported that administration of local anesthetics in vivo induced cell death in muscle cells (10) and neuronal cells (12).…”
mentioning
confidence: 99%
“…However, many studies have shown their cytotoxicity towards several cultured cells (13,14). Cytotoxicity of local anesthetic including lidocaine and prilocaine has been reported on mesenchymal stem cells and osteoblastic cells as well as human oral and tumor cells (15)(16)(17)(18). Even though these local anesthetics have been long used in several complications, there is inadequate information about cytotoxic activity of these agents particularly for dental applications that the use of local anesthetics has been increased.…”
Section: Discussionmentioning
confidence: 99%